Kebutuhan Anak Bedasarkan Al Qur’an Dan Ilmu Kesehatan - Fauriyatul Ilma; Siti Aisyah Siregar; Mega Cahya Dwi Lestari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Children's needs Every individual has basic needs. And every child has special needs. Therefore, parents should understand what the basic needs of a child are. The basic needs of a child include 3 basic needs that are usually described, namely the needs of children in ASAH, ASIH, NURTURING. Needs are everything that man needs to sustain life and to obtain well-being and comfort. Abraham H. Maslow's Hierarchy of Needs takes the form of a pyramid: self-actualization, the need for appreciation, the need for belonging and love, the need for security (salvation), and physiological needs. This scientific paper uses the method of literature review and descriptive writing using primary and secondary sources. The results of this study show that the needs of a child must be considered by parents to achieve appropriate development for children based also on the Qur'an and health science.